KEBIASAAN MAKAN DAN PENGETAHUAN REPRODUKSI REMAJA PUTRI PESERTA PUSAT INFORMASI DAN KONSELING KESEHATAN REPRODUKSI REMAJA (PIK-KRR) - M. Husni Thamrin; Clara Meliyanti Kusharto; Budi Setiawan (Jurnal Gizi dan Pangan, 2008)
The aim of this research was to observe food habit and knowledge of reproduction health of female adolescence participants and non participants of Information Centre and Counseling of Adolescence  Reproduction Health (PIK-KRR) at SMU 1 Liwa and SMK 1 Liwa. Reproduction readiness in adolescence is influenced by physical readiness which is reflected from nutrition and health status and mental readiness in the form of adolescence perception about reproduction health. This research used cross sectional design. The site of the research is determined using purposive sampling. The SMU 1 Liwa was choosen because this school has PIK-KRR and most of the graduates continue their study to the higher level of education, and SMKN Liwa Lampung Barat was chosen because this school does not have PIK-KRR yet and most of the graduates do not continue their study. Spearman’s Correlation and t-test utilized to know whether there were any difference in each variable in SMU and SMK students. The results of the study show that, SMU female adolescence have better reproduction readiness than SMK female adolescence. Therefore it is important for female adolescence to get correct information about nutrition,  and reproduction health through formal or informal ways.